Meningkatkan Hasil Belajar Matematika Siswa Kelas V melalui Penerapan Model Pembelajaran Kooperatif Tipe JIGSAW - Martalena Martalena (Indonesian Institute for Counseling, Education and Therapy (IICET), 2016)
Learning at school was used to be dominated by teacher acting as informant. Learning used at school was also used to be conventional that let students felt no attraction and obtain the unsatistified learning achievement. This research was aimed to improve students’ learning achievement of Mathematics subject by using cooperative learning of Jigsaw. Subject of this research are the fifth grade students at SDN 19 V Koto Kampung Dalam Kabupaten Padang Pariaman. This class action research was held in two cycles. Data of research were obtained through observation and students’ test result. Data were analyzed quantitatively and qualitatively. Researcher set the percentage of learning achievement standard as 70%. Before the implementation, percentage of students’ learning achievement is 50,6%. After cycle I, percentage of students’ learning achievement is 69%. After cycle II, percentage of students’ learning achievement is improved and exceeds the standard, i.e. 80%. These show that implementation of cooperative learning of Jigsaw can improve students’ learning achievement of Mathematics subject.